SISTEM PENDUKUNG KEPUTUSAN SELEKSI CALON KARYAWAN BERDASARKAN HASIL TES PSIKOLOGI KEPRIBADIAN MENGGUNAKAN METODE AHP (Studi Kasus Di KALIMASADA) - Harjanto, Arif (Jurnal Informatika, 2014)
A company is surely careful in selecting the prospective employees which areÂ going to be promoted as employees in the company. A mistake in selecting employees willÂ certainly give a negative influence on the employee performance. Besides evaluating theÂ technical competence, the company also needs to evaluate the personality of theÂ prospective employees. Therefore, it is needed a systematic method and right selection inÂ selecting prospective employees. This research uses Process Hierarchy Analysis (AHP)Â method. The system does an evaluation on psychological test of the prospectiveÂ employeesâ personality, assumed to include the criteria as follows: honesty, loyalty,Â motivation, self-confidence and adaptation or cooperation. The system then will doÂ analysis and evaluation on the test result of the prospective employeesâ personality. TheÂ result of the research is a decision support system model of prospective employee selection based on the psychological test result, so the right selection of prospective employees canÂ determine the real employees of the company as to the position needed. Through theÂ research it can be made a conclusion that the system is feasible to be used by the users andÂ good to be applied.Key Words : AHP, Personality, Employees, Selection, Decision Support System.